Detection of F94L marker in myostatin (MSTN/TaqI) gene of Indonesian Sumba Ongole cattle (Bos indicus) - HARTATI; PUTRA, W P B; SOEWANDI, B D P; ANWAR, S; RATNAWATY, S (The Indian Journal of Animal Sciences, 2022)
Sumba Ongole (SO) cattle are Ongole cattle from India which were imported to Indonesia during the Dutch colonial era and were well adapted on Sumba Island, East Nusa Tenggara, Indonesia. Sumba Ongole (SO) cattle are known for high meat production. This research was conducted to identify one point mutation of g.415C/A (F94L marker) in the myostatin (MSTN) gene (exon 1) using PCR-RFLP method with TaqI restriction enzyme (T*CGA). DNA samples of SO bulls and cows (Total 153) from Sumba Island were used in this study. Results revealed that all samples in this study had CC genotype with C allele as the common allele. The mutation point of g.415C/A was not found in this study. However, one mutation point of g.400G/A was detected in this study without amino acid changes (synonymous). It was concluded that MSTN/TaqI gene in the present study is monomorphic and cannot be used as the genetic marker for productive traits of SO cattle.